Reporting of demographic variables in the Journal of Applied Behavior Analysis. Issue 3 (7th May 2020) - Jones, Stephanie H.; St. Peter, Claire C.; Ruckle, Mary M.
Abstract : Describing demographic variables (e.g., ethnicity/race, socioeconomic status, gender/sex, age) of participants may be important for identifying relations between these variables and behavior‐analytic procedures. Previous research found that demographic variables were underreported in behavior‐analytic studies dealing with particular populations (e.g., children with Autism Spectrum Disorder), interventions (e.g., verbal behavior), or for a subset of demographic variables. We evaluated the extent to which studies recently published in the Journal of Applied Behavior Analysis included descriptions of demographic variables of participants. Demographic variables were often underreported, which may limit the broader dissemination of these behavior‐analytic studies and the development of culturally responsive modifications to behavioral interventions.